EXPERIENCES WITH THE INTRODUCTION OF RARE AND ENDEMIC SPECIES OF TULIPS IN KAZAKHSTAN IN VARIOUS NATURAL ZONES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents the resultsof many years of research into the introductionof 21 species of rare and endemic tulips fromKazakhstan’s flora in four Botanical Gardensin Kazakhstan, Kyrgyzstan and Ukraine.A comparative assessment of the timing offlowering, morphological variability, andsuccess of introduction was carried out, andthe most promising species for each regionwere identified. The first place among themis occupied by Tulipa tarda Stapf, which fullynaturalizes in three regions of the study, withthe exception of the desert Zhezkazgan.
Keywords: tulipa, endemic, botanical garden, reproduction, introduction success, seed productivity.